2010
DOI: 10.1038/ejhg.2010.216
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent genetic alterations in DNA polymerase proofreading and mismatch repair in human colorectal cancer

Abstract: Genomic sequences encoding the 3¢ exonuclease (proofreading) domains of both replicative DNA polymerases, pol delta and pol epsilon, were explored simultaneously in human colorectal carcinomas including six established cell lines. Three unequivocal sequence alterations, including one previously reported, were found, and all these were considered as dysfunctional mutations in light of the local amino-acid sequences. In particular, the F367S mutation found in the POLE gene encoding the pol epsilon catalytic subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 57 publications
5
44
0
Order By: Relevance
“…These tumors with high mutation burden were also notable for having no LOH segments or copy-number variants (CNVs), a feature found in only five other tumors. These features suggest a hypermutator phenotype due to deficiency of mismatch repair (MMR) or polymerase e (POLE) genes (7,8). Consistent with this, these hypermutated tumors showed a paucity of T:A > A:T or C:G > A:T transversions (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…These tumors with high mutation burden were also notable for having no LOH segments or copy-number variants (CNVs), a feature found in only five other tumors. These features suggest a hypermutator phenotype due to deficiency of mismatch repair (MMR) or polymerase e (POLE) genes (7,8). Consistent with this, these hypermutated tumors showed a paucity of T:A > A:T or C:G > A:T transversions (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 54%
“…This distribution is distinct from the remainder (median 36 protein-altering mutations, all <100). Mutator phenotypes in the absence of germ-line mutations in mismatch repair genes have been seen in several other cancers (7,8). These USC tumors are notable for being relatively frequent and for having a uniformly very high number of mutations, more than those seen in 90% of colon cancers with the mutator phenotype (36).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Yoshida et al reported the first POLE mutation in a human colorectal adenocarcinoma [9]. Since then, multiple germline and somatic mutations in POLD1 and POLE have been reported, predominantly in endometrial cancer and CRC.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…Recently, germline and somatic mutations have been described affecting human POLE, encoding the catalytic subunit of polymerase (Pol) e. Evidence from yeast and human studies indicates that Pol e performs the bulk of leading strand DNA replication (5)(6)(7)(8)(9). POLE mutations affecting the proofreading exonuclease are found in 3% of CRC and 7% of EC (6,(10)(11)(12)(13)(14). Mutations affecting the proofreading function of Pol δ, the main lagging strand DNA polymerase, were also observed, although less frequently (6,(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…POLE mutations affecting the proofreading exonuclease are found in 3% of CRC and 7% of EC (6,(10)(11)(12)(13)(14). Mutations affecting the proofreading function of Pol δ, the main lagging strand DNA polymerase, were also observed, although less frequently (6,(10)(11)(12)(13)(14). These observations support the hypothesis that maintenance of DNA replication fidelity restrains neoplasia in humans, as first observed in mice (15)(16)(17), and advance mutator polymerases as important targets to consider for therapeutic intervention.…”
mentioning
confidence: 99%